The selection of strategies for coping with stress at midwife and nurse’s work - Kicia, Mariola; Iwanowicz-Palus, Grażyna; Korżyńska–Piętas, Magdalena; Skurzak, Agnieszka; Krysa, Justyna; Szlendak, Beata (Journal of Education, Health and Sport, 2018)
<span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Nowadays, the interest in issue of occupational stress focuses on the ways of coping and on improving the quality of life, therefore the individual’s activity undertaken in the face of factors causing it. The causes of occupational stress could be divided into these associated with the employee, workplace and its organization. In practice, they all could occur simultaneously. The ubiquity of stress releases human activity to struggle with it. Some people handle it quite well, others bend under its weight.